Discriminator Credibility Dimensions of An Online Acquisition Website – An Analysis of An International Construct on a Specific Romanian Target - Oana Tugulea (CES Working Papers, 2014)
The purpose of this study is to identify credibility dimensions that predict the level of credibility of an online sales clothes Website in Romania. The objectives of this research are: (1) identifying the online sales clothes Websites' credibility dimensions that better discriminate between students to evaluate an online sales clothes Website to be credible or not credible; (2) creating a discriminant function to predict to which of the two analysed groups one user better fits; (3) identifying dimensions that discriminate students between the two groups for two specific situation: second year of study students and third year of study students. For the overall group, the most important discriminator dimension is real world feel. For second year of study students, the only discriminator is trustworthiness. Among the most important discriminating dimensions for third year of study students are real world feel and ease of use.
Keywords: M31; M39; 330; credibility; Website; discriminant analysis; dimension; construct